Tropical and subtropical Asia's valued tree species under threat - Gaisberger, Hannes; Fremout, Tobias; Kettle, Christopher J.; Vinceti, Barbara; Kemalasari, Della; Kanchanarak, Tania; Thomas, Evert; Serra‐Diaz, Josep; Svennin, Jens-Christian; Slik, Ferry; Eiadthong, Wichan; Palanisamy, Kandasamy; et al. (Wiley, 2022)
Tree diversity in Asia's tropical and subtropical forests is central to nature-based solutions. Species vulnerability to multiple threats, which affects the provision of ecosystem services, is poorly understood. We conducted a region-wide, spatially explicit vulnerability assessment (including overexploitation, fire, overgrazing, habitat conversion, and climate change) of 63 socio-economically important tree species selected from national priority lists and validated by an expert network representing 20 countries. Overall, 74% of the most important areas for conservation of these trees fall outside of protected areas, with species severely threatened across 47% of their native ranges. The most imminent threats are overexploitation and habitat conversion, with populations being severely threatened in an average of 24% and 16% of their distribution areas. Optimistically, our results predict relatively limited overall climate change impacts, however, some of the study species are likely to lose more than 15% of their habitat by 2050 because of climate change. We pinpoint specific natural forest areas in Malaysia and Indonesia (Borneo) as hotspots for on-site conservation of forest genetic resources, more than 82% of which do not currently fall within designated protected areas. We also identify degraded lands in Indonesia (Sumatra) as priorities for restoration where planting or assisted natural regeneration will help maintain these species into the future, while croplands in Southern India are highlighted as potentially important agroforestry options. Our study highlights the need for regionally coordinated action for effective conservation and restoration.